Genome-guided prediction of acid resistance mechanisms in acidophilic methanotrophs of phylogenetically deep-rooted Verrucomicrobia isolated from geothermal environments - Neira, Gonzalo; Vergara, Eva; Holmes, David S. (Frontiers in Microbiology, 2022)
Verrucomicrobia are a group of microorganisms that have been proposed to be deeply rooted in the Tree of Life. Some are methanotrophs that oxidize the potent greenhouse gas methane and are thus important in decreasing atmospheric concentrations of the gas, potentially ameliorating climate change. They are widespread in various environments including soil and fresh or marine waters. Recently, a clade of extremely acidophilic Verrucomicrobia, flourishing at pH < 3, were described from high-temperature geothermal ecosystems. This novel group could be of interest for studies about the emergence of life on Earth and to astrobiologists as homologs for possible extraterrestrial life. In this paper, we describe predicted mechanisms for survival of this clade at low pH and suggest its possible evolutionary trajectory from an inferred neutrophilic ancestor. Extreme acidophiles are defined as organisms that thrive in extremely low pH environments (≤ pH 3). Many are polyextremophiles facing high temperatures and high salt as well as low pH. They are important to study for both providing fundamental insights into biological mechanisms of survival and evolution in such extreme environments and for understanding their roles in biotechnological applications such as industrial mineral recovery (bioleaching) and mitigation of acid mine drainage. They are also, potentially, a rich source of novel genes and pathways for the genetic engineering of microbial strains. Acidophiles of the Verrucomicrobia phylum are unique as they are the only known aerobic methanotrophs that can grow optimally under acidic (pH 2–3) and moderately thermophilic conditions (50–60°C). Three moderately thermophilic genera, namely Methylacidiphilum, Methylacidimicrobium, and Ca. Methylacidithermus, have been described in geothermal environments. Most of the investigations of these organisms have focused on their methane oxidizing capabilities (methanotrophy) and use of lanthanides as a protein cofactor, with no extensive study that sheds light on the mechanisms that they use to flourish at extremely low pH. In this paper, we extend the phylogenetic description of this group of acidophiles using whole genome information and we identify several mechanisms, potentially involved in acid resistance, including “first line of defense” mechanisms that impede the entry of protons into the cell. These include the presence of membrane-associated hopanoids, multiple copies of the outer membrane protein (Slp), and inner membrane potassium channels (kup, kdp) that generate a reversed membrane potential repelling the intrusion of protons. Acidophilic Verrucomicrobia also display a wide array of proteins potentially involved in the “second line of defense” where protons that evaded the first line of defense and entered the cell are expelled or neutralized, such as the glutamate decarboxylation (gadAB) and phosphate-uptake systems. An exclusive N-type ATPase F0-F1 was identified only in acidophiles of Verrucomicrobia and is predicted to be a specific adaptation in these organisms. Phylogenetic analyses suggest that many predicted mechanisms are evolutionarily conserved and most likely entered the acidophilic lineage of Verrucomicrobia by vertical descent from a common ancestor. However, it is likely that some defense mechanisms such as gadA and kup entered the acidophilic Verrucomicrobia lineage by horizontal gene transfer.